2016
DOI: 10.1002/adma.201602889
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Single Crystal PtSe2 Nanosheets for Nanoscale Electronics

Abstract: Ultrathin single crystal platinum diselenide (PtSe ) nanosheets are synthesized using H PtCl and Se as the precursors. The electronic properties are first investigated and exhibit p-type transport behavior with the mobility much larger than 7 cm V s . The further investigation on PtSe /MoS var der Waals p-n junction demonstrated that PtSe could be potentially applied in 2D electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
244
2
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 302 publications
(262 citation statements)
references
References 49 publications
(66 reference statements)
13
244
2
3
Order By: Relevance
“…I sd decreases all the time with the V g increasing from ‐80 to 80 V, demonstrating its p‐type behavior. This result is consistent with reported PtSe 2 filmbut inconsistent with mechanical exfoliated PtSe 2 flake . As the bulk PtSe 2 crystal is always synthesized by CVT method with Pt, S, P, Se powders mixed, we suspect it is the Se vacancies or doped atoms like sulfur (S) that play a vital role in determining polarity of PtSe 2 .…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…I sd decreases all the time with the V g increasing from ‐80 to 80 V, demonstrating its p‐type behavior. This result is consistent with reported PtSe 2 filmbut inconsistent with mechanical exfoliated PtSe 2 flake . As the bulk PtSe 2 crystal is always synthesized by CVT method with Pt, S, P, Se powders mixed, we suspect it is the Se vacancies or doped atoms like sulfur (S) that play a vital role in determining polarity of PtSe 2 .…”
Section: Introductionsupporting
confidence: 85%
“…For instance, some large‐area PtSe 2 thin films grown by Yim et al have shown promising gating modulation, yet the quality needs to be improved further. Wang and Zhou realized single‐crystal growth up to 20 μm size, which is of high quality, but still facing the tests such as device fabrication and integrations. Up to now, the transition of metal‐to‐semiconductor and p‐type to other polarities have been only observed in the mechanically exfoliated PtSe 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, developing highly efficient and stable non‐noble metals‐based electrocatalysts to replace precious platinum‐based electrocatalysts becomes an urgent problem. Recently, various non‐noble‐metals‐based electrocatalysts, including transition metal carbides, nitrides, sulfides, oxides, selenides, phosphides, and so on have been demonstrated as promising electrocatalysts for HER.…”
Section: Introductionmentioning
confidence: 99%
“…[18,38] Figure 2a plots the current-voltage (I-V) curve of device in dark. Apparently, this Schottky junction displays a conventional rectifying behavior with a rectification ratio of ≈60 at ± 5 V, which is higher than that of MoS 2 /WS 2 (≈5), [39] PtSe 2 /MoS 2 (15)(16)(17)(18)(19)(20), [40] graphene/In 2 S 3 (≈32), [41] and PtSe 2 /perovskite heterojunctions (≈10), [29] but is slightly lower than that of MoS 2 p-n junction (≈67). [42] Considering the good linear I-V characteristics for Au-PdSe 2 and Au-perovskite achieved ( Figure S4, Supporting Information), the observed rectifying behavior should arise from the Schottky barrier formed at the PdSe 2 /perovskite interface.…”
mentioning
confidence: 99%